Intravesical oxybutynin protects the vesical wall against functional and smooth muscle changes in rabbits with detrusor overactivity - Polido Júnior, Armando [UNESP]; Costa, José Mateus [UNESP]; Munhoz, Tânia [UNESP]; Sampaio, Francisco José; Cardoso, Luiz Eduardo Macedo; Amaro, João Luiz [UNESP] (Springer London Ltd, 2010)
Introduction and hypothesis The aim of this study was to evaluate the protective effect of intravesical oxybutynin on the bladder wall of rabbits with detrusor overactivity and partial bladder outlet obstruction (PBOO).Methods Forty-five North Folk male rabbits were randomly distributed into GI, used as control (n=15), GII-PBOO (n= 14), and GIII-PBOO + intravesical oxybutynin (n=15). Connective tissue and elastic fibers were quantified as volumetric density on picrosirius red and Weigert's Fuchsin-Resorcin-stained sections, respectively.Results In T2, bladder weight was significantly higher in animals in GII and GIII. Smooth muscle bundle diameter was increased by 42% in GII compared with GI (p<0.02). Elastic fibers were significantly higher in GII and GIII as compared with control group. Collagen concentration in GIII and GII was significantly lower than GI (p<0.025).Conclusion Intravesical oxybutynin protected against structural and functional detrusor modifications of the partially obstructed bladder.
Keywords: Rabbits; Collagen; Elastic tissue; Oxybutynin; Overactive bladder